Third delay and associated factors among women who gave birth at public health facilities of Gurage zone, southern Ethiopia - Ayenew Berihun; Teshome Abuka Abebo; Bethelhem Mezgebe Aseffa; Yilkal Simachew; Meskerem Jisso; Yemisrach Shiferaw (BMC, 2023)
Abstract Background The third delay is a delay in accessing emergency obstetric care timely and appropriately once a woman reaches a health facility. The third delay plays a crucial role as an indicator to assess the quality of obstetrics services and is often the leading contributing factor to maternal mortality in developing countries. Although considerable research has been conducted on pre-facility delays in healthcare access, there is a lack of focus on delays experienced upon arrival at health facilities, particularly in Ethiopia and the specific study areas of Gurage zone. This study aimed to assess the magnitude of the third delay and associated factors among women who gave birth at Public Health Facilities of Gurage Zone, Southern Ethiopia. Method A facility-based cross-sectional study was conducted with 558 women who gave birth at public health facilities of Gurage Zone from January 01/2020 to March 30/2020. Multi-stage stratified sampling technique was used to select the nine facilities. The data was collected using a structured interviewer administer questionnaire and an observational checklist. Women who waited more than an hour to receive delivery services after arriving at the health facility were classified as experiencing the third delay. The data were entered and analyzed using Epi Data version 3.1 and SPSS version 20.0 software, respectively. Binary logistic regression was employed to identify the determinant factors for the third delay. Variables having a P-value < 0.25 in the binary analysis were a candidate for multivariable analysis. Variables with P < 0.05 were considered statistically significant. Result The magnitude of the third delay was 193 [(34.8%; 95% CI; (30.8%, 38.8%)]. Complication during labor [AOR = 2.0; 95% CI, (1.4, 3.0)], Presence of functional generator in a health facility [AOR = 2.8; 95% CI, (1.3, 6.3)], level of health institution [AOR = 2.8; 95% CI, (1.04, 7.8)] and BEMONC training in the last two years [AOR = 1.6; 95% CI, (2.0, 6.5)] were significantly associated with third delay. Conclusion The magnitude of third delay was high compared to some low income countries, which shows most of mothers were not getting the service timely after they arrived at the health facility. Equipping health facilities with trained manpower and with necessary materials and infrastructure will contribute to hastening the provision of obstetric care.